PENGARUH PERAN TOTAL QUALITY MANAGEMENT DAN KOMPENSASI TERHADAP KUALITAS SUMBER DAYA MANUSIA PT. DJARUM (STUDI KASUS PADA PABRIK BL 53 KUDUS) - Devita Mayangsari; Sudharto P Hadi; Wahyu Hidayat (Universitas Diponegoro, 2014)
PT Djarum is one of the biggest where the production and operational takes place in Kudus. This research intended to find out impact role of total quality management (X1) and Compensation (X2) to the human resource quality (Y) of BL 53 Factory PT Djarum Kudus. The type of this research is explanatory research, with the population all of BL 53 Factory employee with total of 644 employees. 87 respondents used as sample which counted with Slovin Formula with simple random sampling technique. data collection techniques are interview and questioner. data analysis technique using validity test, reliability test, simple linear regression, double linear regression, T test and F test with SPSS 21.0. Based on regression equation and correlation coefficient can be seen that quality management and compensation had impact to the human resource quality. From the determination coefficient total quality management had 60,8% and compensation had 59,1% of human resource quality.. In Conclusion the better or higher application of either total quality management and compensation will increase the human resource quality.